2009
DOI: 10.1177/0363546509332499
|View full text |Cite
|
Sign up to set email alerts
|

Initial Outcomes of 3-Dimensional Imaging-Based Computer-Assisted Retrograde Drilling of Talar Osteochondral Lesions

Abstract: Arthroscopic treatment of osteochondral lesions of the talus is well established. A retrograde approach does not breach the overlying intact talar cartilage. The results of this follow-up study of 3-dimensional computer navigated drilling are promising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…We believe that antegrade transarticular drilling provides the most accurate method of subchondral bone penetration to address the questionable vascularity of the subchondral fragment. Retrograde drilling has also been described, 23,24 which has the theoretical advantage of not violating the overlying chondral surface but is technically difficult and can result in drill misplacement even with fluoroscopic 2-dimensional navigation. 23 We utilized bioabsorbable implants in all cases of internal fixation in our series, which obviates the need for later hardware removal.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that antegrade transarticular drilling provides the most accurate method of subchondral bone penetration to address the questionable vascularity of the subchondral fragment. Retrograde drilling has also been described, 23,24 which has the theoretical advantage of not violating the overlying chondral surface but is technically difficult and can result in drill misplacement even with fluoroscopic 2-dimensional navigation. 23 We utilized bioabsorbable implants in all cases of internal fixation in our series, which obviates the need for later hardware removal.…”
Section: Discussionmentioning
confidence: 99%
“…For OLTs with the overlying articular cartilage intact, several Level IV studies have reported on the results of antegrade or retrograde drilling without debridement of the lesion. 29,35,55,58,93,99 These studies reported mean postoperative AOFAS scores between 90 and 97 without any complications. One study reported improved arthroscopic appearance of lesions treated with retrograde compared to antegrade drilling, but there was no difference in the AOFAS score.…”
Section: Marrow Stimulationmentioning
confidence: 94%
“…After a mean follow-up of 25 months, significant improvements in clinical scores and the rate of revascularization of impaired areas are reported. 29 …”
Section: Minimally Invasive Treatment Of Acetabular Fracturesmentioning
confidence: 99%